Biochar-amended soil can further sorb atmospheric CO2 for more carbon sequestration - Xiangyang Gui; Xiaoyun Xu; Zehong Zhang; Liyang Hu; Wenfeng Huang; Ling Zhao; Xinde Cao (Communications Earth & Environment)
Abstract Input of biochar into soil is considered as an efficient technology for carbon sequestration. This work is aimed to explore if the extra sorption of carbon dioxide (CO2) exists in the biochar-amended soil, which has not yet received attention. Here we put biochar and mineral-rich biochar into soils to perform laboratory CO2 sorption experiments. Our results demonstrate that all biochar increased soil carbon storage and meanwhile further sorb CO2 for more carbon sequestration. The Ca or Mg originated in biochar could react with more CO2 and eventually be converted into inorganic carbonate minerals in the amended soil. Further, the country-level prediction showed that all cultivated top soils with biochar application in China could achieve 7.38–12.5 billion tons of carbon sequestration and an additional 0.34–2.66 billion tons of CO2 sorption. The results require us to take into consideration of both carbon sink and extra CO2 sorption in the assessment of biochar carbon sequestration potential in soil.